Penerapan Praktik Translanguaging dalam Pembelajaran Bahasa Inggris Disalahsatu Universitas Di Karawang - Vidya Arisandi; Ajat Sudrajat; Yeni Fajrin (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
The purpose of this research is to identify the different forms of translanguaging utilized in general English classes at a university in Karawang, while also exploring the students' attitudes toward the use of translanguaging in the English language classroom. The primary research objective is centered on the types of translanguaging employed in the general English classes at a university. Furthermore, the study aims to ascertain the students' perceptions concerning the application of translanguaging in their general English language learning. This research employs a descriptive qualitative analysis as its methodological approach. The results revealed that a teacher used code-switching to assist students in understanding complex English language concepts. Additionally, the teacher frequently applied translation patterns in general English classes. As for students' perspectives, the findings suggest that the use of translanguaging can enhance their comprehension of the English language when presented by their teacher. Ultimately, this research argues that the implementation of translanguaging strategies by educators is particularly advantageous in augmenting students' comprehension of English language skills within the classroom setting.